Legal review of logging without environmental permits on perum perhutani land in gunung pinang in relation to banten regional regulation number 10 of 2012 concerning environmental protection and management - Sepriandi Putra Sumantri; Asnawi Asnawi; Faturohman Faturohman (Institute Of computer Science (IOCS), 2024)
This study conducts a legal review of logging activities carried out without environmental permits on Perum Perhutani land in Gunung Pinang, examined through the framework of Banten Regional Regulation No. 10 of 2012 concerning Environmental Protection and Management. Using a normative legal research method supplemented by document analysis and comparative review of statutory instruments, the paper identifies the legal obligations imposed by the regional regulation on permit requirements, environmental impact prevention, and restoration duties. The analysis shows that unpermitted logging on state-managed forest land contravenes both regional environmental obligations and broader forestry and environmental statutes it undermines mandates for environmental impact assessment, breach of administrative duties, and triggers liability for environmental damage. The review further highlights gaps in enforcement, ambiguous jurisdictional boundaries between regional and national authorities, and weaknesses in community engagement that permit illicit exploitation to persist. The paper concludes that effective legal response requires coordinated enforcement between Perum Perhutani, regional environmental agencies, and law enforcement; clear procedural guidance on permit processes and sanctions under the regional regulation; and restorative actions including mandatory rehabilitation, sanctions proportionate to harm, and community-based monitoring to prevent recurrence.